HIV Pre-Exposure Prophylaxis (PrEP) Counseling in Germany: Knowledge, Attitudes and Practice in Non-governmental and in Public HIV and STI Testing and Counseling Centers - Kutscha, Frank; Gaskins, Matthew; Sammons, Mary; Nast, Alexander; Werner, Ricardo Niklas (Frontiers in Public Health, 2020)
Background: Providers of sexual health services play an important role in counselling persons at risk of acquiring HIV. The aim of the present study was to investigate the knowledge of and attitudes towards HIV pre-exposure prophylaxis (PrEP) among coun-sellors in non-governmental counselling centres ('NG counselling centres') and in coun-selling centres of the local health authorities ('local health offices') in Germany and to determine the extent to which PrEP plays a role in their current counselling practice. Methods: An anonymous cross-sectional study using an online questionnaire was con-ducted among counsellors from sexual health centres across Germany. All NG counsel-ling centres in Germany offering HIV testing were asked to participate. For each NG counselling centre, a local health office in the same city was also invited. A 'knowledge score' and an 'attitudes score' were calculated from single items on various relevant as-pects. The association of these scores with the proportion of PrEP advice provided pro-actively in sessions with men who have sex with men (MSM) and trans persons who met the German and Austrian guideline criteria for being offered PrEP ('at-risk clients') was quantified. Results: From Oct. to Dec. 2018, 145 counsellors completed the survey. Both self-assessed knowledge of PrEP and attitudes towards PrEP were greater or more positive among counsellors from NG counselling centres compared with counsellors from local health offices [Median knowledge score (range 0-20): 18.0 (IQR=5.0) vs. 14.0 (IQR=4.0), p<0.001; median attitudes score (range 0-20): 18.0 (IQR=4.0) vs. 14.0 (IQR=6.8), p<0.001]. The proportion of PrEP advice provided proactively in sessions with at-risk clients was larger in counselling centres than in local health offices [50.0% (IQR=60.0) vs. 30.0% (IQR=70.0); p=0.003]. The results of the multiple linear regression model indicate that knowledge and attitudes of the individual counsellors, but not the type of centre in which they worked, were independent predictors of the proportion of proactive advice on PrEP. Conclusions: There is room for improvement in the current PrEP counselling practice of sexual health services in Germany. The findings of the present study suggest opportuni-ties to improve the implementation of PrEP as part of a comprehensive HIV prevention strategy.